The Education of Tidal Flood Disaster Mitigation and Environmental Awareness Through Simulation Video Assisted-Problem Based Learning Model - Rizki Riyansyah; Masturi Masturi (Postgraduate, University of Mataram, 2023)
The purpose of this research is to determine the tidal flood disasters mitigation understanding and environmental awareness, as well as to measure the achievement of learning outcomes through the implementation of simulation video assisted problem-based learning. This research used pre-experimental design with one-group pretest-posttest, with the sample is seventh-grade students at Barunawati Junior High School Semarang. The instruments used are multiple-choice questions and Likert scale questionnaire. Rasch model was used to measure the instrument validity and to investigate the attitude scale of environmental awareness due to the learning model implementation, while N-gain test and t-test was used for cognitive analysis of climate change and tidal flood disaster mitigation materials. The knowledge of climate change and tidal flood disaster mitigation increased with N-gain of 0.40 and 0.37, respectively, while the results of t-test for learning outcomes in climate change and tidal flood disaster mitigation showed a significant increase in cognitive learning outcomes, since the video simulation-learning encouraged students to be more active and responsive. Furthermore, the analysis of the attitude scale questionnaire showed an improvement with person measure value from 0.04 (pretest) to 0.84 (posttest). It can be concluded the simulation video assisted problem-based learning model can increase climate change and tidal flood disaster mitigation knowledge, and environmental awareness of students